The Effect of Talent Management and Employee Recognition on Employee Performance - Muhammad Donal Mon; . Jennifer (Inovbiz: Jurnal Inovasi Bisnis, 2022)
This study aims to analyze the effect of learning and development, career management, talent attraction, talent development, talent retention and employee recognition on employee performance. This research is motivated by the decrease in the number of tourist visits that occurred due to the pandemic which had an impact on the ups and downs of employee performance at 4-star hotels in Batam City. This study uses a population of 4-star hotels in Batam City with samples of employees who work at Pacific Palace, Traveloge (Novotel), Planet Holiday and Swiss-Belhotel hotels. This study uses quantitative methods and non-probability sampling techniques through a purposive sampling method involving 285 respondents. The results showed that learning and development, career management, talent interest, talent development, talent retention, and employee recognition have a significant positive influence on employee performance.Keywords:learning and development, career management, talent attraction, talent development, talent retention, employee recognition, employee performance